2010
DOI: 10.1080/13803395.2010.493147
|View full text |Cite
|
Sign up to set email alerts
|

An experimental study of prospective memory in obsessive-compulsive disorder

Abstract: The aim of the present study was to investigate prospective memory (PM) function in patients with obsessive-compulsive disorder (OCD). An event-based PM task was administered to 30 OCD patients and 30 healthy adult participants. For OCD patients, PM instruction produced significantly more cost in terms of reaction time (RT) during the ongoing task. A significant group-experimental condition interaction in ongoing task RTs was found, which suggests that PM instruction loaded an extra cost onto OCD patients' ong… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
10
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 36 publications
4
10
0
Order By: Relevance
“…However, OCD patients were slower in responding to event-based cues compared to healthy controls, which is consistent with previous findings by Racsmany et al (2011). It has been shown that set-shifting is more likely to be involved in time-based PM than in event-based PM Gonneaud et al, 2011;Schnitzspahn et al, 2013).…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…However, OCD patients were slower in responding to event-based cues compared to healthy controls, which is consistent with previous findings by Racsmany et al (2011). It has been shown that set-shifting is more likely to be involved in time-based PM than in event-based PM Gonneaud et al, 2011;Schnitzspahn et al, 2013).…”
Section: Discussionsupporting
confidence: 87%
“…However, neurocognitive functions known to be associated with PM such as retrospective memory and executive functions have been found to be impaired in OCD patients (Abramovitch et al, 2013), suggesting the likelihood of PM deficit in these patients. To date, only four studies have examined PM in OCD patients (Jelinek et al, 2006;Moritz et al, 2006;Harris et al, 2010;Racsmany et al, 2011). The diverse methods and inconsistent results of these studies, however, prevent a clear conclusion about the nature and extent of PM deficits in OCD patients.…”
Section: Introductionmentioning
confidence: 90%
“…remembering to remember (Burgess et al, 2007). Interestingly, OCD has been shown to be associated with aberrant prospective memory (Cuttler and Graf, 2009;Racsmany et al, 2010).…”
Section: Significance Of Superior and Anterior Frontal Cortical Findingsmentioning
confidence: 98%
“…The design of the task allowed us to separately investigate the involvement of the executive system in maintaining and executing a PM response (Racsmány et al, 2011). Based on the results of Burgess et al (2001) we hypothesized that executive monitoring of prospective cues and shifting between ongoing and prospective responses puts an extra load on ongoing task processing when participants are awake and this 6 will be present in an increase of reaction times of the ongoing task.…”
Section: Introductionmentioning
confidence: 99%
“…Intact functioning of PM relies upon a distributed neural network involving the rostral and dorsolateral part of the frontal cortex, the parietal cortex, the hippocampal complex and also the thalamus (Burgess, Quayle, & Frith, 2001;Burgess et al, 2003;Okuda et al, 2001;West, 2008). The injury of this network can produce a serious dysfunction of PM, as it has been detected following extensive frontal lobe lesion and has been identified in a range of psychiatric conditions with deficit of executive frontal lobe functions (Burgess, 2000;Burgess, Veitch, De Lacy Costello, & Shallice, 2000;Elvevåg, Maylor, & Gilbert, 2003;Fortin, Godbout, & Braun, 2002;Fortin, Godbout, & Braum, 2003;Kliegel, Jager, Altgassen, & Shum, 2008;Kondel, 2002;Kumar, Nizamie, & Jahan, 2005;Racsmány, Demeter, Csigó, Harsányi, & Németh, 2011;Schum, Ungvari, Tang, & Leung, 2004). Prospective remembering involves a number of information processing components, such as formation, retention, execution, and evaluation or monitoring of planned actions (see Kliegel, Martin, McDaniel, & Einstein, 2002).…”
Section: Introductionmentioning
confidence: 99%